2001
DOI: 10.1152/jappl.2001.91.3.1207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term microgravity and long-term hindlimb unloading on rat cardiac mass and function

Abstract: The purpose of this study was to test the hypothesis that exposure to short-term microgravity or long-term hindlimb unloading induces cardiac atrophy in male Sprague-Dawley rats. For the microgravity study, rats were subdivided into four groups: preflight (PF, n = 12); flight (Fl, n = 7); flight cage simulation (Sim, n = 6), and vivarium control (Viv, n = 7). Animals in the Fl group were exposed to 7 days of microgravity during the Spacelab 3 mission. Animals in the hindlimb-unloading study were subdivided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…It has been reported that sedentary animals show enhanced sympathoexcitation and altered sympathetic control of blood pressure [42], [43]. Our unloaded rat data are in accordance with what is cited in the literature, even considering differences in the methods of cardiovascular parameter measurements [17], [44], [45]. Unloading caused very similar changes in blood pressure when compared to the group of attached animals, where an increase of diastolic pressure and dramatic rise of SBP was accompanied by a significant perturbation of the day-night cycle.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that sedentary animals show enhanced sympathoexcitation and altered sympathetic control of blood pressure [42], [43]. Our unloaded rat data are in accordance with what is cited in the literature, even considering differences in the methods of cardiovascular parameter measurements [17], [44], [45]. Unloading caused very similar changes in blood pressure when compared to the group of attached animals, where an increase of diastolic pressure and dramatic rise of SBP was accompanied by a significant perturbation of the day-night cycle.…”
Section: Discussionsupporting
confidence: 92%
“…More recent use of magnetic resonance imaging revealed an average 14% reduction in the left ventricular mass of four astronauts following their 10-day mission, supporting the hypothesis that the smaller cardiac size observed after space flight reflected atrophy of myocardial muscle [40]. Contrary to the notion of myocardial atrophy, recent evidence generated from ground-based and flight experiments on animals suggests that smaller myocardial mass may reflect simply the impact of negative caloric balance and body mass routinely observed in astronauts during space flight [41]. Since the loss of body fluids represents a significant amount of body mass reduction in astronauts, it is possible that the apparent reduction in cardiac size represents a loss in tissue water rather than muscle atrophy.…”
Section: Cardiac Structural and Functional Adaptationsmentioning
confidence: 61%
“…The 'hindlimb-unloaded rat' is a model for autonomic deconditioning [28,55]. The rat's hind limbs are bound and its body is suspended using a trolley, so the rat can move about using its forepaws.…”
Section: Orthostatic Syncope S Manmentioning
confidence: 99%
“…This model mimics space flight, which abolishes normal gravitational stress. It causes many alterations similar to those in astronauts [28,55]. Whether or not they (the rats) fainted was not specified.…”
Section: Orthostatic Syncope S Manmentioning
confidence: 99%